History and present day of the formation of the subjectivity of russian tourism - Yarchikovskaya, L.V.; Grigorev, V.I.; Mironova, O.V.; Sharonova, A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the driving forces and threshold values of changes in conditions that shape the subjectivity of tourism at different stages of socio-historical development. Methods and structure of the study. A content analysis of literature, expert forum publications, and statistical data from the Federal State Statistics Service of Russia (FSSS, Rosstat) was conducted. An analysis of scientific concepts and models of Russian tourism development at different ontological stages proves the wave-like nature of the acquisition of subjectivity. As a sociocultural phenomenon, tourism is a product of historical development linked to Russian identity and the development of human essential forces and abilities. Results and conclusions. As a form of culture, tourism (from the French tour, meaning “journey”) came to the fore historically after the publication of the Universal Dictionary of the 19th Century in 1876. In literature, education and science, its essential characteristic reflects the synthetic nature of human activity related to the exploitation of natural resources and new territories [2]. Understanding tourism in the context of biological determinism: ‘nature – man – society’ shows the pendulum-like nature of the migration of animals, birds and marine life. The results of the analysis prove the connection between tourism and the education of man in unity with nature, history and culture.